Adjuvant radiotherapy versus concurrent chemoradiotherapy for the management of high‐risk salivary gland carcinomas. Issue 11 (21st April 2016) - Mifsud, Matthew J.; Tanvetyanon, Tawee; Mccaffrey, Judith C.; Otto, Kristen J.; Padhya, Tapan A.; Kish, Julie; Trotti, Andy M.; Harrison, Louis B.; Caudell, Jimmy J.
Abstract: Background: Given the aggressive behavior of advanced salivary malignancies, the purpose of the current study was to explore the utility of adjuvant chemoradiotherapy (CRT) in this population. Methods: A retrospective study of salivary carcinomas treated from 1998 to 2013 with postoperative CRT (37 patients) or radiotherapy (RT; 103 patients) was completed. Results: The decision to utilize adjuvant CRT versus RT was influenced by tumor grade and histology, cervical lymph node status, surgical margins, and perineural invasion. In both treatment cohorts, high locoregional control rates were obtained (79% for CRT vs 91% for RT; p = .031). Multivariate Cox regression analysis did not identify a difference in 3‐year progression‐free survival (PFS) with the use of CRT versus RT (hazard ratio [HR] = 0.783; 95% confidence interval [CI] = 0.396–1.549; p = .482). Conclusion: Until prospective evidence is available, such as from Radiation Therapy Oncology Group 1008, the standard use of CRT for advanced salivary malignancies cannot be recommended. © 2016 Wiley Periodicals, Inc. Head Neck 38 : 1708–1716, 2016